Foot-and-Mouth Disease in Swine - Preben Willeberg (Frontiers Research Topics, 2017)
Foot-and-mouth disease (FMD) is one of the most devastating diseases of livestock. The research topic here features nine studies supplementing the state-of-the art of the knowledge on the pathogenesis and epidemiology of FMD in swine.